Reading comprehension strategies of the EFAL learners in the FET phase: teacher perspectives - Zano, Kufakunesu (Penerbit Universiti Kebangsaan Malaysia, 2020)
The level of English First Additional Language (EFAL) Reading Comprehension competence among school learners in some schools in South Africa is a concern. English is used as a medium of teaching and learning in most South African public schools although the majority of these learners are EFAL speakers. To counter this anxiety, reading comprehension interventions become handy. This study aimed to explore the reading comprehension strategies of South African high school EFAL learners in the FET phase. The study employed a non-experimental quantitative design to collect data. The general version 7.0 questionnaire on strategy inventory of language learning (SILL) Oxford (1990) on identifying strategies learners use in reading comprehension was used. The sampling frame was 80 grade 11 high school EFAL learners in South Africa. The results of the study show that EFAL learners use multiple language learning strategies to enhance their understanding of English in an EFAL setting. It is difficult to strike consistency in language learning strategies because the choice of a language learning strategy differs from one EFAL learner to another. It remains important that language practitioners become aware of the need to equip EFAL teachers and learners as they strive to sharpen EFAL learners’ language learning skills.